Risk factors for community-acquired pneumonia among inpatients with mental disorders in a tertiary general hospital - Han, Jingjing; Shen, Meiyu; Wan, Qirong; Lv, Zhihua; Xiao, Ling; Wang, Gaohua (Frontiers in Psychiatry, 2022)
Introduction: Community-acquired pneumonia (CAP) is an important cause of hospitalization and death in patients with mental disorders. It is critical to understand the risk factors of CAP and determine prevention strategies to reduce CAP. The aim of this study is to explore the characteristics of inpatients with mental disorders who have CAP and analyze the risk factors. Methods: This retrospective study included 16,934 inpatients with mental disorders who were admitted for the first time to a tertiary general hospital between January 2017 and July 2021 (excluding January 2020 to May 2020). Risk factors for CAP were identified by logistic regression analysis after propensity score matching (PSM, 1:4) for age, gender, and BMI. Results: The CAP rate of inpatients with mental disorders was 1.78%. Inpatients who had CAP had a significantly prolonged hospital stay, and were more often admitted to a closed ward or the ICU. After PSM, the multivariable analysis revealed that clozapine use (OR=3.212, 95%CI=1.744-5.915, P<0.001), schizophrenia spectrum disorder (OR=2.785, 95%CI=1.684-4.607, P<0.001), alcohol consumption (OR=2.549, 95%CI=1.586-4.096, P<0.001), cardiovascular disease (OR=2.299, 95%CI=1.362-3.879, P=0.002), Charlson comorbidity index [CCI) ≥3 (OR=2.092, 95%CI=1.342-3.260, P=0.001], organic mental disorder (OR=1.941, 95%CI=1.194-3.156, P=0.007), antipsychotic drug use (OR=1.886, 95%CI=1.312-2.711, P=0.001), unmarried status (OR=1.720, 95%CI=1.164¬-2.541, P=0.006) and junior high school education (OR=1.591, 95%CI=1.010-2.508, P=0.045) were independent risk factors for CAP in inpatients with mental disorders. Conclusion: CAP was common in inpatients with mental disorders. Patients with mental disorders have unique risk factors for CAP. Further research is required to explore the relationship and mechanism between different mental disorders, antipsychotic drugs and CAP.